Effects of nitrogen concentration variation in molybdenum nitride underlayer for spin valves - Kim, J.; Choi, Y.; Jo, S.; Kim, Y. T.; Lee, C. W. (ELSEVIER, 2007)
We have studied magnetic and thermal properties of MoN. lms with different nitrogen concentrations. When a small amount of nitrogen is incorporated into the Mo-underlayer of a top-type spin valve, we do not observe any significant thermal degradation of its magnetic properties after annealing at 220 degrees C. The magnetoresistance ratio of the as-deposited spin-valve structure is 7.0% and slightly increases to 7.5 % even at the annealing temperature of 220 degrees C. The amount of nitrogen in the MoN underlayer seems to affect the texture growth of NiFe ( 1 1 1) and to improve the magnetic characteristics of the spin valve. From the XPS analysis of MoN thin. lms and XRD analysis of NiFe. lms grown on the MoN underlayer, it is concluded that spin-valve structure grown on the MoN underlayer with N-2 gas-flow rate of 5 sccm is more stable than that grown with N-2 gas-flow rate of 1 sccm. (C) 2006 Elsevier B. V. All rights reserved.